2019
DOI: 10.1093/icvts/ivz156
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of left atrial appendage occlusion using the AtriClip device: a systematic review

Abstract: Atrial fibrillation increases lifetime stroke risk. The left atrial appendage (LAA) is thought to be the source of embolic strokes in up to 90% of cases, and occlusion of the LAA may be safer than the alternative of oral anticoagulation. Occlusion devices, such as the AtriClipTM (AtriCure, Mason, OH, USA) enable safe and reproducible epicardial clipping of the LAA. A systematic review was performed in May 2018, based on the Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines, using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 37 publications
2
56
0
1
Order By: Relevance
“…Left atrial appendage occlusion (LAAO) is recommended for patients with atrial fibrillation undergoing elective cardiac surgery 1 . Studies are reporting excellent outcomes for the AtriClip LAAO device without major device‐related complications in several clinical trials 2 . Here, we report the first case of delayed severe coronary artery stenosis with NSTEMI after implantation of the AtriClip device during open‐heart surgery with sternotomy.…”
Section: Introductionmentioning
confidence: 94%
“…Left atrial appendage occlusion (LAAO) is recommended for patients with atrial fibrillation undergoing elective cardiac surgery 1 . Studies are reporting excellent outcomes for the AtriClip LAAO device without major device‐related complications in several clinical trials 2 . Here, we report the first case of delayed severe coronary artery stenosis with NSTEMI after implantation of the AtriClip device during open‐heart surgery with sternotomy.…”
Section: Introductionmentioning
confidence: 94%
“…Various refinements beyond pulmonary vein isolation, including complex fractionated atrial electrograms (CFAEs), focal impulse and rotor modulation (FIRM), electrocardiographic imaging (ECGI), have been explored but met with variable, inconsistent success (Weiss et al, 2016). For left atrial appendage occlusion, the AtriClip device has gained increasing popularity over the last decade as a safe and efficacious alternative to surgical closure and can be easily deployed during concomitant open chest surgery or standalone minimally invasive procedure (Ellis et al, 2017;Caliskan et al, 2018;Toale et al, 2019).…”
Section: Evolving Therapeutic Strategiesmentioning
confidence: 99%
“…Quinidine, one of the oldest antiarrhythmic drugs, was used extensively in the 20th century for a variety of arrhythmias, including AF ( Askey, 1946 ; McMillan and Welfare, 1947 ; Wegria, 1947 ). The combination of quinidine and verapamil has similar efficacy in preventing AF recurrences as sotalol but with better safety profile ( Fetsch et al, 2004 ; Patten et al, 2004 ).…”
Section: Early Antiarrhythmic Drugs For Rhythm Controlmentioning
confidence: 99%
“…A longer-term dataset published in 2014 by Emmert et al showed good long-term stability of the device, without any dislodgement, out to 36 months [52]. Subsequently, many studies have been conducted to show the high levels of success and safety in deploying the AtriClip device, including a recent systematic review of 11 studies by Toale et al [53]. At present, there is a current lack of adequately powered, prospective, randomised studies to accurately assess the reduction in risk of stroke with the use of the AtriClip; however, there is very encouraging evidence from smaller-scale or non-randomised studies, a large registry study, and a systematic review [42,[53][54][55][56].…”
Section: Atriclip For Laaeimentioning
confidence: 99%